Applied Calculus
posted by Jacob .
Find the derivative of the function:
(x^(3)8)/(x^(2)+9)

The rule is the denominator times the derivative of the numerator minus the numerator times the derivative of the denominator AND then put this answer over the denominator squared.
The deriv. of the numerator is 3x^2 and the deriv of the denom. is 2x
Can you finish from here? 
y = (x^38)/(x^2+9)
If y = u/v, y' = (vu'  uv')/v^2, so
y = ((3x^2)(x^2+9)  (x^38)(2x))/(x^2+9)^2
= (3x^4 + 27x^2  2x^4 + 16x)/(x^2+9)^2
= (x^4 + 27x^2 + 16x)/(x^2+9)^2 
Yeah, I was forgetful and forgot it was the Quotient Rule. Thank you all, I got it!

just curious  if you forgot about the quotient rule, what did you try?
Respond to this Question
Similar Questions

calculus
Find the derivative of the function using the definition of derivative. g(t)= 9/sqrt(t) g'(t)= state the domain of the function and the domain of the derivative (use interval notation) 
Applied Calculus
Find the derivative of the function f by using the rules of differentiation. f(x)=340 
Applied Calculus
Find the derivative of the function: f(x)=(x^2+9)/square roote of x 
Applied Calculus
Find the derivative of the function. g(t) = ((8t + 10)^2)*(((10t^2)  7)^3) I am supposed to use The Chain Rule. However, I am confused as to how to do this. 
Applied Calculus
Find the derivative of this function: g(t)=(8t+10)^2*(10t^27)^3 Using the Chain Rule. 
Applied Calculus
Find the first and second derivative of the function: x/(7x+10) Using quotient rule. This is part of my homework in the section named "Higher Order Derivatives". I am confused on getting the second derivative, as I found the first … 
Applied Calculus
Find the third derivative of the function: (5t+4)^(1/2) 
Applied Calculus
Find the third derivative of the function: g(t)=square root of 7t+5 
Applied Calculus
Find the third derivative of the function: g(t)=square root of 7t+5 
Calculus
Hello I need help with this excersise of derivative of a inverse function. The excersise says: If f(x+2)=x^3+1 and g(x)=f(arctg x), find the derivative of the inverse function of g(x) and then calculate (g^1 (9))'[the derivative of …